E-Modul Materi Thaharah melalui Pendekatan Sains Teknologi Islam untuk Meningkatkan Sustainable Living Peserta Didik - Syafa'ah, Devanisa Rofi'atusy; Meishanti, Ospa Pea Yuanita; Roziqin, Muhammad Khoirur (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
This study aims to: (1) describe the feasibility of Thaharah e-module material through the Islamic technology science approach, (2) describe the feasibility of Thaharah e-module media through the Islamic technology science approach, (3) describe the attractiveness of Thaharah e-module media through the Islamic technology science approach. The type of research used in this study is R&D (Research and Development) with the ADDIE development model. The subjects of this study were grade VIII students at SMPN 2 Jombang. The results of this study indicate that: (1) The results of data analysis of learning material expert validation are 85.3%, if converted into the achievement percentage table, it is included in the very feasible category, (2) The results of data analysis of learning media expert validation are 92%, if converted into the table it is included in the very feasible category, (3) The results of data analysis of students' responses are 81.9%, if converted into the into the table it is included in the very attractive category. So, according to the two validators of material experts and learning media experts also the response of students, e-module of thaharah material through the Islamic science technology approach gets a very feasible category.